Epithelioid angiomyolipoma of the liver: a case report - Soo Yeon Lee (Clinical and Molecular Hepatology, 2017)
Epithelioid angiomyolipoma (EAML) of liver is a rare neoplasm. Hepatic EAML is often misdiagnosed as other neoplasms such as hepatocellular carcinoma due to non-specific clinical and radiologic features. The morphologic features under microscope and immunohistochemistry staining profile are important in the diagnosis EAML. Here, we report a case of 52-year-old man who found 1.2 cm mass in liver by routine checkup. On the impression of hepatocellular carcinoma, lateral sectionectomy of the liver was done. Microscopically, the tumor is composed of predominant epithelioid cells with vascular component and foamy cells. These cells were positive for HMB45, MelanA, and smooth muscle actin and negative for epithelial membrane antigen. The final diagnosis was hepatic EAML.